Pakistan’s Higher Education System—What went Wrong and How to Fix it. (The Pakistan Development Review, 2009)
None of Pakistan’s 50+ public universities comes even close to being a university in the real sense of the word. Compared to universities in India and Iran, the quality of both teaching and research is far poorer. Most university “teaching” amounts to a mere dictation of notes which the teacher had copied down when he was a student in the same department, examinations are tests of memory, student indiscipline is rampant, and a large number of teachers commit academic fraud without ever getting punished. In some universities the actual number of teaching days in a year adds up to less than half the officially required number. Some campuses are run by gangs of hoodlums and harbour known criminals, while others have had Rangers with machine guns on continuous patrol for years on end. Common wisdom has always been that increased funding can solve all, or at least most, of the systemic problems that bedevil higher education in Pakistan. But Pakistan offers an instructive counterexample: a many-fold increase in university funding from 2002-2008 resulted in, at best, only marginal improvements in a few parts of the higher education sector. This violation of “commonsense” points to the need for some fresh thinking. The analysis of Pakistan’s higher education system divides naturally into three parts: consideration of the necessary background; understanding the meaning of university quality in the Pakistani context; and exploring the space of solutions.